"Simple" Aggregation‐Induced Emission Luminogens for Nondoped Solution‐Processed Organic Light‐Emitting Diodes with Emission Close to Pure Red in the Standard Red, Green, and Blue Gamut. Issue 6 (9th May 2021) - Zhang, Tianfu; Zhou, Zhicong; Zheng, Zheng; Zhang, Jianyu; Yu, Ying; Lam, Jacky W. Y.; Halpert, Jonathan E.; Tang, Ben Zhong
Abstract : Development of simple and efficient red emissive luminogens is desirable yet challenging for optoelectronic devices due to the limited molecular design and the difficulties of synthesis. Red emitting molecules possess large π‐conjugated systems, which permit quenching in the solid state due to π–π stacking and are detrimental to the performance of devices. Furthermore, traditional red emitters usually exhibit emission far from pure red in the standard red, green, and blue (sRGB) gamut. Herein, two red luminogens, DCMa and DCIs, with aggregation‐induced emission (AIE) characteristics based on simple donor–acceptor (D–A) structures are explored. They show high fluorescence quantum yields (QYs) of 13.2% and 7.8% in the film state. Efficient nondoped solution‐processed organic light emitting diodes (OLEDs) with a configuration of indium tin oxide (ITO)/poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS)/poly[(9, 9‐dioctylfluorenyl‐2, 7‐diyl)‐ co ‐(4, 40‐( N ‐(4‐sec‐butylphenyl)diphenylamine)] (TFB)/DCMa or DCIs/(1, 3, 5‐tris(2‐ N ‐phenylbenzimidazolyl)benzene) (TPBi)/LiF/Al are fabricated, which emit red electroluminescence at 652 and 711 nm, respectively. Furthermore, they exhibit International Commission on Illumination (CIE) coordinates of (0.63, 0.36) and (0.64, 0.35), respectively, which are close to the value of the primary red color (0.63, 0.34) according to the digital television standard. These results of small molecules DCMa and DCIs suggest future methods for designing new red emitters for nondoped solution‐processed OLEDs. Abstract : Two red luminogens with aggregation‐induced emission (AIE) characteristics are explored. Efficient nondoped solution‐processed organic light emitting diodes (OLEDs) are fabricated and emit bright red electroluminescence. Furthermore, they exhibit International Commission on Illumination (CIE) coordinates of (0.63, 0.36) and (0.64, 0.35), respectively, which are close to that of the primary red color according to the digital television standard.